EFEKTIVITAS PENGGUNAAN PHET SEBAGAI MEDIA PEMBELAJARAN FISIKA UNTUK MENINGKATKAN PENGUASAAN MATERI FLUIDA STATIS - Rumakur, Bahdiana Efriyanti; Kereh, Cicylia Triratna; Latupeirissa, Asry N (Atom : Jurnal Riset Mahasiswa, 2023)
This study aims to determine the effectiveness of using PhET as a medium for learning physics to increase mastery of inert fluid material for students in class X State High School 4 spooky eastern part. The type of research used is descriptive quantitative with a research design that is a one-group pretest and posttest. This research was conducted with a population of students of class X IPA at SMA Negeri 4 SBT. The sample of class X IPA-1 was 21 students who were taken at random. The data in this study were collected through test and non-test instruments, test instruments in the form of pretest and posttest, and non-test test instruments in the form of student worksheets (LKPD). The results showed that in the initial test, 100% of students failed the qualification, with an average achievement score of 7.83. The maximum achievement score is 25.8, while the minimum is 1.72. The results of the analysis of cognitive aspects during the learning process using PhET as a learning medium showed that the average student achievement score was 92.23, which was an excellent qualification. These results are collected based on completing the questions in the LKPD. The ability of students to learn shows a change. The average score of the student's final test achievement reached 91.17, which was an excellent qualification. For the N-Gain test, results obtained 0.8, which is in the high category. In the effectiveness test that the results of the calculation of the t-count 48.45 and t-table 2.080 with a significant level of 5%, the t-count value is 48.45 > t-table 2,080 where 21 students (100%) are declared effective. Thus it can be concluded that the use of PhET as a practical physics learning media to improve students' mastery of static fluid material class X State High School 4 SBT